Use of soil-rock mixtures in dam construction - Caldeira, L. (2014)
The employment of non-traditional materials such as soil–rock mixtures, for economic and environmental reasons, in the construction of earthworks poses some new challenges for compaction techniques and their control as well as for the determination of the characteristics of the embankment that result from the compaction method. Those characteristics experience important changes according to the relative percentages of the existing fractions. Usually, this kind of material results from bulky rock extraction without explosives, and it can include some large size particles (greater than 0.5 m). In addition, the measured deformations associated with these materials have been larger than expected. For the execution control of the soil–rock mixtures from the Odelouca dam borrow areas, a series of vibratory and standard compaction tests was performed to estimate reference values for the maximum dry density and optimum water content of these materials and a new methodology was proposed. Odelouca dam is a zoned embankment dam, 76 m high, with clayey soil in the core and weathered schist with a significant fraction of oversized particles in the shells. This paper presents the results of the compaction control as well as the dam performance during the construction and first filling phases as a validation of implemented construction procedures.